Comparison of Different Combinations of Irradiation Mode and Jaw Width in Helical Tomotherapy for Nasopharyngeal Carcinoma - Zhang, Jun; Peng, Yinglin; Ding, Shouliang; Zhu, Jinhan; Liu, Yimei; Chen, Meining; Sun, Wenzhao; Zhou, Linghong; Deng, Xiaowu (Frontiers in Oncology, 2020)
Purpose: To aid in the selection of a suitable combination of irradiation mode and jaw width in helical tomotherapy (HT) for the treatment of nasopharyngeal carcinoma (NPC). Materials and Methods: 20 patients with NPC who underwent radiotherapy were retrospectively selected. Four plans using a jaw width of 2.5 or 5 cm in dynamic jaw (DJ) or fix jaw (FJ) modes for irradiation were designed (2.5DJ, 2.5FJ, 5.0DJ, and 5.0FJ). The dose parameters of planning target volume (PTV) and organs at risk (OARs) of the plans were compared and analyzed，as well as the beam on time(BOT) and monitor unit (MU). The plans in each group were ranked by scoring the doses received by the OARs and the superity was assessed in combination with the planned BOT and MU. Results: The prescribed dose coverage of PTV met the clinical requirements for all plans in the four groups. The groups using a 2.5 cm jaw width or a DJ mode provided better protection to most OARs, particularly for those at the longitudinal edges of the PTV (P<0.05). The 2.5DJ group had the best ranking for OAR-dose, followed by the 2.5FJ and 5.0DJ groups with a same score. The BOT and MU of the groups using a 5.0-cm jaw width reduced nearly 45% comparing to those of the 2.5-cm jaw groups. Conclusion: 2.5DJ has the best dose distribution, while 5.0DJ has satisfactory dose distribution and less BOT and MU that related to the leakage dose. Both 2.5DJ or 5DJ were recommended for HT treatment plan for NPC based on the center workload.